Expression of Stylistic Convergence in Translation - Khudoyberdieva Nigora Sherali qizi (Periodica Journal, 2022)
Being able to fully reflect the stylistic convergence in the translation is important in conveying the main ideas expressed in the translation to the reader. However, it will not be possible to fully translate the stylistic convergence due to incomplete understanding of the content of the work and differences in the language structure. According to translators, maintaining stylistic convergence in translation is the main criterion of adequate translation, but it is impossible to fully translate stylistic convergence in all translations, and in some texts, stylistic tools used in the original are partially translated, and in some cases, they are omitted
Keywords: convergence; adequate translation; basic model; divergence